Strong Start Innovation: Equitable Outcomes Across Public and Privately Insured Clients Receiving Birth Center Care. (8th December 2022) - Jolles, Diana; Hoehn‐Velasco, Lauren; Ross, Lisa; Stapleton, Susan; Joseph, Jennie; Alliman, Jill; Bauer, Kate; Marcelle, Ebony; Wright, Jennifer
Abstract : Introduction: The Birth Center model of care is a health care delivery innovation in its fourth decade of demonstration across the United States. The purpose of this research was to evaluate the model's potential for decreasing poverty‐related health disparities among childbearing families. Methods: Between 2013 and 2017, 26, 259 childbearing people received care within the 45 Center for Medicare and Medicaid Innovation Strong Start birth center sites. Secondary analysis of the prospective American Association of Birth Centers Perinatal Data Registry was conducted. Descriptive statistics described sociobehavioral, medical risk factors, and core clinical outcomes to inform the logistic regression model. Privately insured consumers were independently compared with 2 subgroups of Medicaid beneficiaries: Strong Start enrollees (midwifery‐led care with peer counselors) and non‐Strong Start Medicaid beneficiaries (midwifery‐led care without peer counselors). Results: After controlling for medical risk factors, Strong Start Medicaid beneficiaries achieved similar outcomes to privately insured consumers with no significant differences in maternal or newborn outcomes between groups. Perinatal outcomes included induction of labor (adjusted odds ratio [aOR], 0.86; 95% CI 0.61‐1.13), epidural analgesia use (aOR, 1.00; 95% CI, 0.68‐1.48), cesarean birth (aOR, 1.16; 95% CI, 0.87‐1.53), exclusive breastfeeding on discharge (aOR, 1.11; 95% CI, 0.48‐2.56), low Apgar score at 5 minutes (aOR, 1.23; 95% CI, 0.86‐1.83), low birth weight (aOR, 1.12; 95% CI, 0.77‐1.64), and antepartum transfer of care after the first prenatal appointment (aOR, 1.53; 95% CI, 0.97‐2.40). Medicaid beneficiaries who were not enrolled in the Strong Start midwifery‐led, peer counselor program demonstrated similar results except for having higher epidural analgesia use (aOR, 1.30; 95% CI, 1.10‐1.53) and significantly lower exclusive breastfeeding on discharge (aOR, 0.57; 95% CI, 0.40‐0.81) than their privately insured counterparts. Discussion: The midwifery‐led birth center model of care complemented by peer counselors demonstrated a pathway to achieve health equity.